2014
DOI: 10.1128/aem.03327-13
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in Klebsiella oxytoca in Response to Low Oxidoreduction Potential, as Revealed by Comparative Proteomic Profiling Integrated with Flux Balance Analysis

Abstract: dOxidoreduction potential (ORP) is an important physiological parameter for biochemical production in anaerobic or microaerobic processes. However, the effect of ORP on cellular physiology remains largely unknown, which hampers the design of engineering strategies targeting proteins associated with ORP response. Here we characterized the effect of altering ORP in a 1,3-propanediol producer, Klebsiella oxytoca, by comparative proteomic profiling combined with flux balance analysis. Decreasing the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…) and other bacteria included in the bacterial indicator group (Zhu et al . ). I propose these conditions collectively promote similar types of physiological damage, to which the more sensitive subpopulation (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and other bacteria included in the bacterial indicator group (Zhu et al . ). I propose these conditions collectively promote similar types of physiological damage, to which the more sensitive subpopulation (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Anaerobic conditions and ORP as low as those in the UF and APPZ have been shown to cause cellular damage and reduction in growth rates in E. coli (Riondet et al 1999(Riondet et al , 2000Lee et al 2001) and other bacteria included in the bacterial indicator group (Zhu et al 2014). I propose these conditions collectively promote similar types of physiological damage, to which the more sensitive subpopulation (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study by Zhu et al ([ 2014 ]) reported the effects of altered oxido-reduction potential (ORP) in protein expression by combined proteomic profiling and flux balance analysis in K. oxytoca cultures. The authors stated that the ratio of metabolic fluxes through reductive and oxidative pathways of glycerol degradation were sensitive to changes in extracellular ORP, and reductive pathways were channelled by low ORP.…”
Section: Discussionmentioning
confidence: 99%
“…L. plantarum ST-III was cultivated in TYC medium under air conditions and the extracellular oxido-reduction potential (ORP) was determined as described in previous studies (Zhu et al, 2014;Huang et al, 2017). In brief, after being cultured, 20 ml culture broth was filtered under vacuum through a 0.8-μm mixed cellulose ester membrane, and the filtrate was diluted appropriately to determine the ORP.…”
Section: Determination Of Extracellular Oxido-reduction Potentialmentioning
confidence: 99%